2018
DOI: 10.1101/246389
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Direct imaging of the circular chromosome in a live bacterium

Abstract: New assays for quantitative imaging [1][2][3][4][5][6] and sequencing [7][8][9][10][11] have yielded great progress towards understanding the organizational principles of chromosomes. Yet, even for the well-studied model bacterium Escherichia coli, many basic questions remain unresolved regarding chromosomal (sub-)structure 2,11 , its mechanics 1,2,12 and dynamics 13,14 , and the link between

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 36 publications
10
37
0
Order By: Relevance
“…2). This may be consistent with recent images of the E. coli nucleoid showing a donut shape in round cells, in which the ter region appears less condensed than the rest of the chromosome in a MatP-dependent way 43 . Higher α coefficient may be linked to the MatP-mediated exclusion of MukBEF from ter 13,15,16 .…”
Section: Discussionsupporting
confidence: 92%
“…2). This may be consistent with recent images of the E. coli nucleoid showing a donut shape in round cells, in which the ter region appears less condensed than the rest of the chromosome in a MatP-dependent way 43 . Higher α coefficient may be linked to the MatP-mediated exclusion of MukBEF from ter 13,15,16 .…”
Section: Discussionsupporting
confidence: 92%
“…2G). This observation is in line with recent finding that MatP proteins modulate the actions of MukBEF (Lioy et al, 2018;Nolivos et al, 2016) and are responsible for inducing a thin Ter region (Wu et al, 2018), rather than condensing the Ter region (Dupaigne et al, 2012;Mercier et al, 2008). Unlike Fis and SlmA, the effect of MatP is apparent across all cell lengths, showing that its role in condensing the chromosome acts in parallel to the effect of boundary-confinement and is relevant to the nucleoid size in regular cells at steady-state growth conditions.…”
supporting
confidence: 92%
“…3E yielded saturation values of 6.7 and 4.9 μm for two crowder densities, close to the experimentally observed value, which is gratifying in view of the simplicity of the model. While our elementary model with a uniform loop size and constant crowder density thus captures the experimentally observed trends remarkably well, further modeling of the profile of the nucleoid-cell length relation will benefit from refinements by additional factors including the heterogeneous and dynamic nature of both the DNA loop distribution (Fisher et al, 2013;Postow et al, 2004;van Loenhout et al, 2012;Wu et al, 2018) and the cytosolic particle sizes (Parry et al, 2014).…”
Section: Polymer Modeling Captures the Sizing And Positioning Of Nuclmentioning
confidence: 79%
See 1 more Smart Citation
“…These compact nucleoprotein structures are similar to the LacI‐mediated DNA topological barriers that efficiently block DNA supercoiling diffusion . Furthermore, a recent study showed that Fis protein was able to help form transient and dynamic chromosome domain boundaries/topological barriers to block supercoiling diffusion . All these results support the hypothesis that Fis protein can form topological barriers along the bacterial genome and block supercoiling diffusion.…”
supporting
confidence: 62%